2018
DOI: 10.1007/s10654-018-0359-y
|View full text |Cite
|
Sign up to set email alerts
|

Coffee or Tea? A prospective cohort study on the associations of coffee and tea intake with overall and cause-specific mortality in men versus women

Abstract: Coffee and tea intake have been associated with reduced mortality, but no studies have investigated possible substitution effects. The relationship of mortality with coffee, tea, and substituting coffee with tea was investigated in the Netherlands Cohort Study. In 1986, 120,852 men and women aged 55-69 years provided information on dietary and lifestyle habits. Mortality follow-up until 1996 consisted of linkage to Statistics Netherlands. Multivariate case-cohort analyses were based on 8665 deaths and 3166 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 55 publications
0
21
1
Order By: Relevance
“…Although a dose response association between green tea intake and the risk of CRC was examined in previous epidemiological studies [12,32,33], we found different risk patterns for CRC and the amount of green tea consumption depending on smoking and drinking status and a high-inflammatory diet. High green tea consumption decreased the risk of CRC, but moderate green tea consumption increased the risk of CRC in ever-smokers, ever-drinkers and the high-DII group.…”
Section: Discussioncontrasting
confidence: 59%
“…Although a dose response association between green tea intake and the risk of CRC was examined in previous epidemiological studies [12,32,33], we found different risk patterns for CRC and the amount of green tea consumption depending on smoking and drinking status and a high-inflammatory diet. High green tea consumption decreased the risk of CRC, but moderate green tea consumption increased the risk of CRC in ever-smokers, ever-drinkers and the high-DII group.…”
Section: Discussioncontrasting
confidence: 59%
“…Additionally, two prospective cohort studies found that drinking green tea could reduce the risk of CVD death with HR 0.86 (95% CI: 0.77–0.97) in middle-aged and elderly Chinese adults [28]. In a Netherlands cohort study, tea consumption was found to be remarkably and nonlinearly associated with the decreased CVD risk in men, with those drinking 2–3 cups/day possessing the lowest HR (0.72, 95% CI: 0.57–0.91) [29]. In addition, a Dongfeng-Tongji cohort study found that green tea consumption could reduce the risk of CHD (HR = 0.89, 95% CI: 0.81–0.98) in the middle-aged and older Chinese population [30].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…As with all the other living organisms, the heterogeneity of compounds required for the development of a plant is remarkable: macronutrients are constituted by lipids, glucides, and proteins, while micronutrients are mainly represented by minerals, vitamins, and polyphenols. Camellia sinensis is the plant whose leaves are used for the manufacturing of tea, one of the most consumed beverage all over the world, well known for its health-promoting intake, mainly correlated to the antioxidant activities of polyphenols [ 1 , 2 ]. Polyphenols (secondary metabolites generally involved in defense against ultraviolet radiation or aggression by pathogens [ 3 ]) are responsible for tea color, astringency, and flavor [ 4 ].…”
Section: Introductionmentioning
confidence: 99%